Effectiveness of Implementation and Management of E-Makaryo Application in Reducing Unemployment Rate in Central Java Province - Salsabila Puspitasari, Azzahra; Intan Setianingrum, Putri; Wahyu Setiawan, Abraham; Hidayati, Retno; Kusumawardhani, Amie (Indonesian Association for Public Administration (IAPA), 2023)
The E-Makaryo application is a labor market application that is presented online and developed by the Central Java Provincial Government. The E-Makaryo application which was formed through the Decree of the Head of the Central Java Provincial Manpower and Transmigration Office Number 1024 of 2020 concerning the Online Job Exchange and Labor Market Information Service System (E-Makaryo) in 2020 is managed directly by the Government. Central Java Provincial Manpower and Transmigration Office. In this regulation, there are 9 main objectives for its implementation in the hope of reducing unemployment in Central Java Province. The purpose of this study is to determine the level of effectiveness of the E-Makaryo application in reducing unemployment in Central Java. This research will involve application providers and also users, namely the people of Central Java. The research method uses descriptive qualitative method with data collection techniques through in-depth observation and other supporting data. The theory used in this research is Hoffman and Bateson's development theory of services (action, effort, or performance). Another theory used is the 4 characteristics of effectiveness proposed by (Steers, 1985). The results of this study indicate that the application of the E-Makaryo online job market has not reached the maximum stage caused by the lack of activities to encourage people to recognize and use the E-Makaryo application. Other factors such as supporting information on the application system and service channel factors are still many obstacles in using the E-Makaryo application considering that the application still often causes errors. Based on these problems, researchers have suggestions for application providers to actively conduct socialization to introduce and encourage people, especially Central Java, to use the E-Makaryo application. In addition, application providers can also continue to improve the system by completing the information needed by the community.